2010
DOI: 10.1161/atvbaha.110.207654
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Phospholipid Transfer Protein Deficiency in Mice Is Associated With a Reduced Thrombotic Response to Acute Intravascular Oxidative Stress

Abstract: Objective-Earlier in vitro studies suggested a putative role for the plasma phospholipid transfer protein (PLTP) in the modulation of blood coagulation. The effect of PLTP expression on blood coagulation under both basal and oxidative stress conditions was compared here in wild-type and PLTP-deficient (PLTPϪ/Ϫ) mice. Methods and Results-Under basal conditions, PLTP deficiency was associated with an extended tail bleeding time despite a significant depletion of vascular ␣-tocopherol content and an impairment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Ten years ago, it was reported that PLTP KO mice exhibit a longer clotting time (tail bleeding) compared with WT mice and that this could be related to a relative decrease in PS externalization via a reduction in the vitamin E level in erythrocytes (74). Consistent with this result, Desrumaux et al (75) reported that plasma PLTP deficiency is associated with a reduced thrombotic response to acute intravascular oxidative stress. Thus, PLTP seems to be involved in hypercoagulation.…”
Section: Pltp and Thrombosismentioning
confidence: 56%
“…Ten years ago, it was reported that PLTP KO mice exhibit a longer clotting time (tail bleeding) compared with WT mice and that this could be related to a relative decrease in PS externalization via a reduction in the vitamin E level in erythrocytes (74). Consistent with this result, Desrumaux et al (75) reported that plasma PLTP deficiency is associated with a reduced thrombotic response to acute intravascular oxidative stress. Thus, PLTP seems to be involved in hypercoagulation.…”
Section: Pltp and Thrombosismentioning
confidence: 56%
“…In all four backgrounds, the PLTP defi ciency increased oxidative damage ( 97 ). PLTP defi ciency also decreased ␣ -tocopherol concentrations in both the brain and the vascular wall, decreased hepatic ␣ -tocopherol concentrations, and led to an increase in apoB degradation ( 98 ).…”
Section: Hepatic Secretion Of ␣ -Tocopherol Into Plasmamentioning
confidence: 95%
“…From LPS aggregates to HDL in vitro [14] From HDL to LDL in vitro [15] From bacterial blebs to HDL in vitro [16] From LPS aggregates to HDL in vivo [17] (b) Biochemical/biological pathways [38,39] Brain physiology [40] Reproductive biology [41] Reverse LPS transport Innate immunity [17] Cancer treatment [42] (apolipoprotein B)-containing lipoprotein production by the liver [23,25,26,45]. In addition, vitamin E redistribution between lipoproteins and the vascular wall could contribute to PLTP atherogenicity [13,43,46].…”
Section: Introductionmentioning
confidence: 99%